2011
DOI: 10.1002/chem.201102005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Imidazolium–Anion Interaction through the Anion‐Templated Construction of Interpenetrated and Interlocked Assemblies

Abstract: The interaction between imidazolium cations and coordinating anions is investigated through the anion-templated assembly of interpenetrated and interlocked structures. The orientation of the imidazolium motif with respect to anion binding, and hence the hydrogen bond donor arrangement, was varied in acyclic receptors, interpenetrated assemblies, and the first mono-imidazolium interlocked systems. Their anion recognition properties and co-conformations were studied by solution-phase 1H NMR investigations, solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
1
28
0
1
Order By: Relevance
“…Very recently, bis(triazole)pyridinium analogues of these species have been prepared, with both the rotaxane [77] and catenane [78] showing selectivity for the halides (Cl À to I À ) over dihydrogen phosphate in CDCl 3 /CD 3 OD (1:1). The pyridinium axle motifs have also been exchanged for imidazolium [118] and triazolium [119] in the construction of further rotaxanes. A rotaxane has also been synthesized where the axle component-an iodotriazolium-coordinates to the .…”
Section: Anion-templated Rotaxanes and Catenanesmentioning
confidence: 99%
“…Very recently, bis(triazole)pyridinium analogues of these species have been prepared, with both the rotaxane [77] and catenane [78] showing selectivity for the halides (Cl À to I À ) over dihydrogen phosphate in CDCl 3 /CD 3 OD (1:1). The pyridinium axle motifs have also been exchanged for imidazolium [118] and triazolium [119] in the construction of further rotaxanes. A rotaxane has also been synthesized where the axle component-an iodotriazolium-coordinates to the .…”
Section: Anion-templated Rotaxanes and Catenanesmentioning
confidence: 99%
“…Based on numerous examples of 2‐haloimidazolium‐related halogen bonding (XB) in crystal structures, it is presumed that halogen bonding provides a major contribution to its binding affinity to Lewis bases in solution. Although other non‐covalent interactions, such as anion–π,, ion pairing and hydrogen bonding (HB) may also contribute to the overall binding strength, this has not yet been thoroughly assessed and is only rarely discussed (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the cis isomer of a hexapyrrolic calix[4]pyrrole binds anions in a mixed‐binding mode by a combination of hydrogen bonding and anion–π interactions, whereas the trans isomer displays only hydrogen‐bonding interactions 21. In this context, we are interested in pursuing this goal to create receptors in which selectivity does not arise from size‐ and shape matching with a particular anionic guest, but rather from the combined intrinsic anion preference of two distinct noncovalent interactions 2224. Herein, we describe a receptor capable of anion binding by a combination of both hydrogen‐bonding and anion–π interactions with a 1,2,3‐triazolium binding site, in which one ring acts as a hydrogen‐bond receptor and the other as an anion–π receptor.…”
Section: Introductionmentioning
confidence: 99%
“…[21] In this context, we are interested in pursuing this goal to create receptors in which selectivity does not arise from size-and shapem atching with ap articular anionic guest, but rather from the combined intrinsic anion preference of two distinct noncovalent interactions. [22][23][24] Herein, we describe ar eceptor capable of anion binding by ac ombination of both hydrogen-bonding and anion-p interactions with a1 ,2,3-triazolium binding site, in which one ring acts as ah ydrogen-bond receptor and the other as an anion-p receptor. This novel dual role of the 1,2,3-triazolium ring as an anionbinding site has no precedent in the literature.…”
Section: Introductionmentioning
confidence: 99%